STUDY ON THE FLAVONOIDS, TOCOPHEROL AND ASCORBIC ACID CONTENT IN RAW AND ROASTED ARABICA COFFEE BEANS - Arzoo, Shaista; Badr, Nawal Al; Masri, Soheir Al; Obead, Manal A A Bin (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2018)
In this study we examined flavonoids, alpha- tocopherol and ascorbic acid content in raw and roasted Arabica coffee beans. Rutin, Quercetin, Kaempferol and Isorhamnetin are the various flavonoids determined in this study and it has been found that the roasted coffee exhibited lesser content of flavonoids than unroasted coffee and the concentration of Rutin was highest among all identified flavonoids. Similarly α-tocopherol and ascorbic acid was also highest in green beans. Green Legamy Arabica coffee showed highest concentration of all flavonoids and ascorbic acid and also provide maximum percentage of Recommended Dietary Allowance for flavonoids, ascorbic acid and alpha tocopherol.